Lean mass deficits, vitamin D status and exercise capacity in children and young adults after Fontan palliation. Issue 21 (27th June 2014) - Avitabile, Catherine M; Leonard, Mary B; Zemel, Babette S; Brodsky, Jill L; Lee, Dale; Dodds, Kathryn; Hayden-Rush, Christina; Whitehead, Kevin K; Goldmuntz, Elizabeth; Paridon, Stephen M; Rychik, Jack; Goldberg, David J
Abstract : Objective: We sought to evaluate body composition in children and young adults with Fontan physiology. Leg lean mass (LM) deficits correlate with diminished exercise capacity in other populations and may contribute to exercise limitations in this cohort. Methods: This cross-sectional study included whole body dual energy X-ray absorptiometry scans in 50 Fontan participants ≥5 years, and measures of peak oxygen consumption (VO2 ) in 28. Whole body and leg LM (a measure of skeletal muscle) were converted to sex- and race-specific Z-scores, relative to age and stature, based on 992 healthy reference participants. Results: Median age was 11.5 (range 5.1–33.5) years at 9.3 (1.1–26.7) years from Fontan. Height Z-scores were lower in Fontan compared with reference participants (−0.47±1.08 vs 0.25±0.93, p<0.0001). Body mass index Z-scores were similar (0.15±0.98 vs 0.35±1.02, p=0.18). LM Z-scores were lower in Fontan compared with reference participants (whole body LM −0.33±0.77 vs 0.00±0.74, p=0.003; leg LM −0.89±0.91 vs 0.00±0.89, p<0.0001). LM Z-scores were not associated with age or Fontan characteristics. Leg LM Z-scores were lower in vitamin D deficient versus sufficient Fontan participants (−1.47±0.63 vs −0.71±0.92, p=0.01). Median per cent predicted peak VO2 was 81% (range 13%–113%) and was associated with leg LM Z-scores (r=0.54, p=0.003). Conclusions: Following Fontan, children and young adults are shorter than their peers and have significant LM deficits. Skeletal muscle deficits were associated with vitamin D deficiency and reduced exercise capacity. Future studies should examine the progression of these deficits to further understand the contribution of peripheral musculature to Fontan exercise capacity.